Association of endothelial nitric oxide synthase Glu298Asp gene polymorphism in psoriasis cases with hypertension - Ogretmen, Zerrin (Ann Saudi Med, 2014)
BACKGROUND AND OBJECTIVES: Psoriasis is a common autoimmune-mediated chronic, inflammatory skin disease. Although, the molecular mechanism is not completely understood, psoriasis is caused by genetic and non-genetic parameters. The current study aimed (1) to define genotype and allele frequency of endothelial nitric oxide synthase (eNOS Glu298Asp) gene polymorphism in hypertensive and/or non-hypertensive psoriatic patients (2) to investigate the possible relationship between the eNOS Glu298Asp polymorphism and the risk of hypertension among psoriatic patients in the Turkish population. DESIGN AND SETTINGS: This cross-sectional, case-control study was performed between March 2010 and November 2012 at the University hospital in Çanakkale, Turkey PATIENTS AND METHODS: Gene profiles of 75 psoriatic patients (21 hypertensive and 54 normotensive patients) and 55 healthy (normotensive and non-psoriatic) volunteers were compared. Peripheral blood-EDTA samples were used for total genomic DNA isolation and genotyping. Target eNOS gene was genotyped for patients and control groups by real-time PCR melting-curve analysis system (LightCycler 2.0, Roche, Germany, and results were compared statistically. RESULTS: An increased T allele frequency in eNOS Glu298Asp single-nucleotide polymorphism (SNP) was determined in psoriatic patients when compared with normotensive non-psoriatic healthy volunteers (OR 2.3, CI 1.14–3.99), (P=.017). The T allele frequency was also found to be increased in hypertensive psoriatic patients when compared with healthy volunteers (4.83-fold increased, 95% CI 1.62–14.43 ([P=.003]) and normotensive psoriatic patients (3.03-fold increased, 95% CI 1.03–8.94 [P=.041]), respectively. CONCLUSION: The current preliminary results suggested that there was a correlation between eNOS Glu298Asp polymorphism and hypertension among psoriatic patients in the Turkish population. The T allele frequency of eNOS Glu298Asp SNP was different in hypertensive psoriatic patients, and the difference was statistically significant when compared with the normotensive psoriatic patients and healthy controls. These results need to be confirmed by large-scale studies.